2016
DOI: 10.1371/journal.pmed.1002124
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled Intermittent Screening with Rapid Diagnostic Tests and Treatment with Dihydroartemisinin-Piperaquine versus Intermittent Preventive Therapy with Sulfadoxine-Pyrimethamine for Malaria in Pregnancy in Malawi: An Open-Label Randomized Controlled Trial

Abstract: BackgroundIn Africa, most plasmodium infections during pregnancy remain asymptomatic, yet are associated with maternal anemia and low birthweight. WHO recommends intermittent preventive therapy in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP). However, sulfadoxine-pyrimethamine (SP) efficacy is threatened by high-level parasite resistance. We conducted a trial to evaluate the efficacy and safety of scheduled intermittent screening with malaria rapid diagnostic tests (RDTs) and treatment of RDT-positive wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 37 publications
(46 reference statements)
2
108
1
1
Order By: Relevance
“…This is important given the results of the current trial which found that RDTs only detected around 45% of PCR-positive infections in paucigravidae and 30% in multigravidae; as women were treated according to RDT result, this may explain the higher prevalence of malaria infections at delivery in the ISTp-DP arm [22]. However, it is important to note that the biological impact of such low-level parasitaemia during pregnancy is unclear [37, 38] and the incidence of clinical malaria was not significantly different between the trial arms [22]. Compliance with RDT result was not an issue in the trial setting but it is unclear whether or not non-compliance would be observed in a screening strategy involving asymptomatic pregnant women under routine conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is important given the results of the current trial which found that RDTs only detected around 45% of PCR-positive infections in paucigravidae and 30% in multigravidae; as women were treated according to RDT result, this may explain the higher prevalence of malaria infections at delivery in the ISTp-DP arm [22]. However, it is important to note that the biological impact of such low-level parasitaemia during pregnancy is unclear [37, 38] and the incidence of clinical malaria was not significantly different between the trial arms [22]. Compliance with RDT result was not an issue in the trial setting but it is unclear whether or not non-compliance would be observed in a screening strategy involving asymptomatic pregnant women under routine conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Both health workers and pregnant women also perceived that DP had fewer side effects than SP for women enrolled in the trial. This is interesting, given that the trial found no significant differences in clinical malaria or adverse events between the two arms [22]. Sentiments regarding the effectiveness of either drug by both health workers and pregnant women influenced their opinions of the concept of prevention versus cure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations